The clinical significance of iron metabolism disorders in patients with high activity of rheumatoid arthritis - E. A. Galushko; A. S. Semashko; A. M. Lila (Научно-практическая ревматология)
Aim – to study the clinical manifestations of rheumatoid arthritis (RA) and the spectrum of concomitant diseases, depending on the level of hepcidin in patients with high inflammatory activity.Material and methods. The analysis included 78 patients (48.9±15.5 years) with RA, disease duration of 108 [48; 204] months. All patients were diagnosed with high or medium inflammatory activity of the disease (DAS28-ESR (Disease Activity Score 28 with erythrocyte sedimentation rate detection – 5.2). Indicators of iron metabolism, levels of hepcidin and interleukin 6 were determined. Three subgroups of patients were identified: subgroup I – with serum hepcidin levels below the reference values (less than 40 pg/ml); subgroup II – with hepcidin levels within the reference values (40–120 pg/ml); subgroup III – patients with high hepcidin levels (more than 120 pg/ml).Results. It was found that in RA with high inflammatory activity, regardless of the hemoglobin level, disorders in iron metabolism were noted in 83% of cases. Reduced serum hepcidin levels were diagnosed in 40% of cases (subgroup I), on average, very high hepcidin values were detected in every second (n=34; subgroup III). The main clinical manifestations of RA, DAS28 activity and duration of the disease were comparable in all three subgroups. The largest number of concomitant diseases were diagnosed in RA patients with high levels of hepcidin. Chronic obstructive pulmonary disease (26%), endocrine pathology – 22% (diabetes mellitus, thyroid diseases, obesity), chronic kidney disease (21%) and cardiovascular disease (60%) were significantly more common (p<0.05). With iron deficiency, the most common pathology was gastrointestinal tract damage – 35% (erosive gastritis, peptic ulcer of the stomach and duodenum, etc.), the second most common was pathology of the cardiovascular system (32%). In the same subgroup, one in ten had a change of two classes of bDMARDs/tsDMARDs by the time of the study.Conclusion. The results of this study illustrate the need for further study of the pathogenetic pathways of iron metabolism disorders in order to form scientifically sound approaches to personalized treatment of a wide range of immunoinflammatory rheumatic diseases, including RA.